The recovery process utilizing Erikson's stages of human development. - Vogel-Scibilia SE; McNulty KC; Baxter B; Miller S; Dine M; Frese FJ III (Community Mental Health Journal, 2009)
Of current interest to the field are clinical frameworks that foster recovery. The authors offer a psycho-developmental model that parallels Erik Erikson's theory of human development, and theorize that the process of psychiatric recovery involves a psychic reworking of these fundamental steps. Understanding recovery in this context allows the client and the practitioner of psychiatric rehabilitation to design and implement a coherent treatment strategy.